2009
DOI: 10.1002/adfm.200801844
|View full text |Cite
|
Sign up to set email alerts
|

PEI–PEG–Chitosan‐Copolymer‐Coated Iron Oxide Nanoparticles for Safe Gene Delivery: Synthesis, Complexation, and Transfection

Abstract: Gene therapy offers the potential of mediating disease through modification of specific cellular functions of target cells. However, effective transport of nucleic acids to target cells with minimal side effects remains a challenge despite the use of unique viral and non-viral delivery approaches. Here we present a non-viral nanoparticle gene carrier that demonstrates effective gene delivery and transfection both in vitro and in vivo. The nanoparticle system (NP-CP-PEI) is made of a superparamagnetic iron oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
271
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 363 publications
(274 citation statements)
references
References 45 publications
3
271
0
Order By: Relevance
“…Results showed that the majority of the delivered nanoparticles accumulated in the liver (86%) and spleen (6.2%) within 1 h following intravenous injection. 59 Felabeled iron nanoparticles could be cleared out from the liver and spleen with a half-life of 3-4 days. 59 Fe was then found to be incorporated into hemoglobin of erythrocytes.…”
Section: Biodistribution Safety and Degradationmentioning
confidence: 99%
See 3 more Smart Citations
“…Results showed that the majority of the delivered nanoparticles accumulated in the liver (86%) and spleen (6.2%) within 1 h following intravenous injection. 59 Felabeled iron nanoparticles could be cleared out from the liver and spleen with a half-life of 3-4 days. 59 Fe was then found to be incorporated into hemoglobin of erythrocytes.…”
Section: Biodistribution Safety and Degradationmentioning
confidence: 99%
“…59 Felabeled iron nanoparticles could be cleared out from the liver and spleen with a half-life of 3-4 days. 59 Fe was then found to be incorporated into hemoglobin of erythrocytes. Even with a high dose of 3000 μmol Fe/kg that is 150-times over the in vivo imaging dose, there was no acute or subacute toxic effects in rats or beagle dogs [70].…”
Section: Biodistribution Safety and Degradationmentioning
confidence: 99%
See 2 more Smart Citations
“…[334] This method may lead to robust conjugation of payload molecules as well as improving the stability of MNPs and reducing the nonspecific uptake of biomolecule to have longer blood circulation times for biomedical applications. [335] SPIONs coated with copolymer of PEG-gchitosan-g-PEI were developed by Kievit et al [336] for delivering DNA. They reported a good stabilization of SPIONs along with efficient DNA complexation and gene transfection achieved Polyethylene glycol (PEG) Easy to functionalize, hydrophilic, improves biocompatibility and blood circulation time as well as internalization efficiency by reducing uptake, non-antigenic, and non-immunogenic properties.…”
Section: Copolymersmentioning
confidence: 99%